HARMONI DI LINGKUNGAN TROPIS LEMBAB : KEBERHASILAN BANGUNAN KOLONIAL (DIMENSI: Journal of Architecture and Built Environment, 2004)
The paper attempts to look at the linkage factors between the socio-cultural-physical phenomena, and spatial formation in the settlement of a tropical region. Three types of house form in high and low density settlements, namely the traditional, the colonial and the modern, were selected as the case studies. First, the paper shows the change and constancy of traditional values in the development of the settlement and house forms from traditional to modern. Then using a computer simulation, thermal performances of the houses are calculated and analysed according to the spatial formation and thermal behaviour of the building elements. The potential of each houses in countering the heat is compared and discussed according to spatial formation and the benefit of using such building elements. It is likely that the colonial house resulted better indoor condition than the others. Abstract in Bahasa Indonesia : Interaksi antara phenomena sosio-kultural-pisikal dan pembentukan ruang (spatial formation) dilingkungan hunian didaerah tropis lembab terus berkembang, diikuti dengan perubahan pembentukan ruang. Tiga studi kasus diangkat untuk mengungkap aspek pembentukan ruang yaitu hunian tradisional dan hunian kolonial semuanya di kampung mewakili lingkungan dengan padat hunian. Sedangkan hunian standar pemerintah mewakili hunian modern dilingkungan modern, dengan kepadatan rendah. Keunikan lingkungan diketengahkan pada proses hubungan antar aspek pembentuk ruang dari tradisional hingga ke modern. Selanjutnya proses simulasi komputer dilakukan untuk mengetahui peran tatanan ruang dan elemen bangunan dalam pembentukan kondisi thermal bangunan. Nilai-nilai yang berlanjut dan yang tidak berlanjut pada tatanan ruang dan ditandai sebagai salah satu penyebab perubahan kondisi thermal. Dalam hal ini bangunan kolonial mempunyai kelebihan bila dibanding yang lain.Kata kunci: Harmoni, perilaku termal, pendinginan pasif, formasi spasial.